2009
DOI: 10.1108/01409170910965215
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the behavioral intention to use enterprise resource planning systems

Abstract: PurposeThe purpose of this paper is to examine various factors affecting users' behavioral intention to use (BIU) enterprise resource planning (ERP) systems, based on data from 75 potential end‐users of ERP systems.Design/methodology/approachA survey methodology is used to gather data. The research model is constructed based on the findings of the previous studies.FindingsThe results indicate that subjective norms, perceived usefulness (PU) and education level are determinants of BIU the system. In addition, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
78
1
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(105 citation statements)
references
References 71 publications
12
78
1
14
Order By: Relevance
“…This result is surprising and does not align with the traditional TAM model by F. D. Davis et al (1989). On the other hand, hypotheses H3 and H4 are supported, which is in agreement with the research findings of Bueno and Salmeron (2008), Calisir et al (2009), andSamander andAbdul Rahman (2014). The results seem to reinforce the rather important observation that if things are not perceived as easy to use then they are not considered useful.…”
Section: Findings and Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This result is surprising and does not align with the traditional TAM model by F. D. Davis et al (1989). On the other hand, hypotheses H3 and H4 are supported, which is in agreement with the research findings of Bueno and Salmeron (2008), Calisir et al (2009), andSamander andAbdul Rahman (2014). The results seem to reinforce the rather important observation that if things are not perceived as easy to use then they are not considered useful.…”
Section: Findings and Discussionsupporting
confidence: 78%
“…A number of researchers (Calisir, Gumussoy, & Bayram, 2009;Sūpulniece et al, 2013;Usmanij, Khosla, & Chu, 2013) have suggested that user satisfaction is one of the key factors leading to the success of an Information System (IS) and that interface usability can be seen as one of the factors that influences end user satisfaction (Babaian, Lucas, & Topi, 2006;Šūpulniece et al, 2013). A user friendly interface decreases system complexity and impacts on user behavior (Bueno & Salmeron, 2008).…”
Section: H4: Attitude Towards Usage Has a Positive Effect On The Behamentioning
confidence: 99%
“…Undoubtedly, the moderating effects of gender have been statistically confirmed in adoption and acceptance studies of different information technology domains and settings (Lichtenstein & Williamson, 2006;Zhang, 2009;Hasan, 2010;Riquelme & Rios, 2010;Van Slyke et al, 2010;Dong & Zhang, 2011). Apparently, there has been no conclusive evidence to suggest that gender differences always have a pronounced effect in relation to the research conducted in the context of adoption of a new technological innovation (Bigne et al, 2005;Cyr & Bonannni, 2005;Calisir et al, 2009;Dong & Zhang, 2011 (Bigne et al, 2005;Zhou et al, 2007;Lip-Sam & Hock-Eam, 2011). However, the moderating effects of gender have not largely been investigated in the context of m-healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these add other external variables to the original TAM model that are considered to be interesting for the research. Thus, it is frequently used in studies on ERP implementation and use in companies [50,52,[72][73][74][75][76][77][78][79][80][81][82], applications for e-commerce [83], file digitization systems [84], Internet banking [85], mobile social gaming [86], and e-learning platforms [62,[87][88][89][90], among many other sectors.…”
Section: Adoption Modelsmentioning
confidence: 99%